Methods in bioengineering : 3D tissue engineering - Berthiaume, François; Morgan, Jeffrey Robert (Artech House methods in bioengineering series., 2010)
This practical book is part of the new Artech House Methods in Bioengineering series - volumes designed to offer detailed guidance on authoritative methods for addressing specific bioengineering challenges. Written and edited by recognized experts in the field, each book provides research engineers, scientists, and students with step-by-step procedures, clear examples, and effective ways to overcome problems that may be encountered. Tissue engineering is an emerging field that involves the combination of materials, cells, and other signals or growth factors to generate new tissue that can be used to repair or replace damaged tissues due to injury or disease. This groundbreaking volume presents the latest methods and protocols for systematically building tissues in 3D configuration outside the body, as well as providing techniques that modulate repair and regeneration processes that occur "in situ" (in their natural or original place). -- Publisher's description.